Study on mechanism of temperature-modulated polyphenolic biosynthesis in cigar tobacco leaves - Kang, Jiahao; Fu, Bo; Yan, Xiaoxiao; Xiao, Menglan; Yang, Weili; Zhao, Mingqin (Frontiers in Plant Science, 2025)
Cigars as an economic crop, inappropriate growth temperature can detrimentally affect cigar quality, yet our knowledge about the response of cigar tobacco leaves (CTLs) to such stressors remains limited. We subjected CTLs to prolonged mild low-temperature and high-temperature treatments and systematically assessed oxidative stress markers, antioxidant enzyme activities, phenolic and flavonoid accumulation, and transcriptomic dynamics. Weighted gene co-expression network analysis (WGCNA) and correlation-based approaches were used to identify key genes and regulators.This study revealed that both long-term mild low and high temperatures in CTLs triggered excessive production of reactive oxygen species (ROS) and disrupted antioxidant enzyme systems. Exposure to low temperatures resulted in increased accumulation of phenolic and flavonoids, while high temperatures were associated with either negative or negligible effects on these metabolites. Moreover, low temperatures significantly stimulated phenylpropanoid biosynthesis, in contrast to the negative effects observed at high temperatures. Correlation analysis indicated that NtMYB12-1, NtMYB12-2, and NtMYB12-3 likely acted as crucial regulators in the modulation of enzymes involved in phenylpropanoid biosynthesis under variable temperature conditions. Furthermore, weighted co-expression network analysis identified that NtCHS-6, Nt4CL-6, and NtPAL-1 worked as central hub genes in phenylpropanoid biosynthesis-related modules. This study provides a deeper understanding of the complex theoretical framework of phenylpropanoid biosynthesis in CTLs when exposed to fluctuating temperatures, offering valuable insights for the cultivation of high-quality cigar products.